If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(2 + -3x) = -5x + -3 5 + (2 * -1 + -3x * -1) = -5x + -3 5 + (-2 + 3x) = -5x + -3 Combine like terms: 5 + -2 = 3 3 + 3x = -5x + -3 Reorder the terms: 3 + 3x = -3 + -5x Solving 3 + 3x = -3 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 3 + 3x + 5x = -3 + -5x + 5x Combine like terms: 3x + 5x = 8x 3 + 8x = -3 + -5x + 5x Combine like terms: -5x + 5x = 0 3 + 8x = -3 + 0 3 + 8x = -3 Add '-3' to each side of the equation. 3 + -3 + 8x = -3 + -3 Combine like terms: 3 + -3 = 0 0 + 8x = -3 + -3 8x = -3 + -3 Combine like terms: -3 + -3 = -6 8x = -6 Divide each side by '8'. x = -0.75 Simplifying x = -0.75
| f(-5)=6x-9 | | 3(x+150)+5x=4730 | | 3x-12=9x+48 | | -6+-3s+11-5s= | | 16x-16+4=30 | | 3y+5x-60=180 | | 0.6g+1=5 | | -2x-5(-3x-7)=-121 | | f(4)=6x-9 | | -4x+9=-3(2x+1) | | 1.5(2-x)=-1.5x | | 500-20x=500 | | 5+6x=6+2h | | 8y+14-3y=5+3y | | 10+-4x=-38 | | -144H-4+9-9H=135H+5 | | 0.6(100-x)+1.4x=0.5(92) | | -70-x=26+3x | | 2y-8x=24 | | 36(16x^5+24x^4+28x^3-8x^2-3x-5)=0 | | -4(3x+1)+13x=9 | | -.01(x-4)=.6 | | 3times(6-x)=27 | | 300-7(4(3+5))+27= | | x^2+xy+y^2=6 | | -0.009x^2+0.265x-0.951=0 | | 14.88=d-34.76 | | 11x*13x=27 | | 7(n-6)=-140 | | .3x-.5x-9=1 | | 500=0.22x+220 | | -11=4+3x |